2021
DOI: 10.3390/dj9120151
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perceived Risk, and Preventive Behaviors amidst Covid-19 Pandemic among Dental Students in Malaysia

Abstract: Purpose: Coronavirus disease 19 (COVID-19) has affected dental education in Malaysia. However, studies on dental students’ knowledge, perception, and behaviors with regards to COVID-19 are very limited. Thus, this study aims to determine the knowledge status, perceived risk, and preventive behaviors of dental students in Malaysia regarding COVID-19. Methods: A cross-sectional study was conducted among students from 13 dental schools across Malaysia using online questionnaires. Results: From 355 respondents, 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…We found that the vast majority of the students in this study were worried about carrying the infection back to their families (Table 1 ).In accordance with a Malaysian study in 2021, 89.3% of respondents were concerned about their family's health [ 33 ]. Also Consistent to a study in China, college students were more worried about their elder family members [ 34 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that the vast majority of the students in this study were worried about carrying the infection back to their families (Table 1 ).In accordance with a Malaysian study in 2021, 89.3% of respondents were concerned about their family's health [ 33 ]. Also Consistent to a study in China, college students were more worried about their elder family members [ 34 ].…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, a multinational study in 2020 recorded the same results [ 45 ]. In contrast to Malaysian study in 2021 reported no significant difference in the mean preventive behavior scores when comparisons were made between students across years and phases of study [ 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…Thus, college students, as a highly information-sensitive group (9), have deeply recognized the seriousness of the epidemic and the adverse effects of COVID-19 infection. Besides, on-campus students may consider the campus environment relatively safer compared to off-campus (49). Moreover, Chinese universities mostly adopt closed management and strict prevention and control measures, so college students' daily lives and social mobility are restricted in many ways.…”
Section: Figurementioning
confidence: 99%
“…
The coronavirus disease (COVID-19) has instigated a nationwide "lockdown" in Malaysia which began on 18 March 2020 upon the Movement Control Order, issued by the government. Even though the whole country was not in a total lockdown, many sectors have been badly affected including the education sector, in which all education institutions were indefinitely ordered for closure by the government (Ismail et al, 2021). Because of that, education institutions were inevitably urged to resume teaching and learning activities remotely via online mode.
Kulliyyahof Dentistry (KOD), International Islamic University Malaysia (IIUM) is a dental faculty (kulliyyah) which is located in Kuantan, Pahang, a state in the East Coast of Malaysia.During that period, the Kulliyyah have consolidated on the following approaches in order to advocate the Ministry of Higher Education 's order for remote e-learning:
…”
mentioning
confidence: 99%
“…The coronavirus disease (COVID-19) has instigated a nationwide "lockdown" in Malaysia which began on 18 March 2020 upon the Movement Control Order, issued by the government. Even though the whole country was not in a total lockdown, many sectors have been badly affected including the education sector, in which all education institutions were indefinitely ordered for closure by the government (Ismail et al, 2021). Because of that, education institutions were inevitably urged to resume teaching and learning activities remotely via online mode.…”
mentioning
confidence: 99%